Status Hukum Internasional dalam Sistem Hukum di Indonesia - Wisnu Aryo Dewanto (Fakultas Hukum Universitas Gadjah Mada, 2009)
A rule of international law is regarded as non-self-executing in the Indonesian legal system. It means the international legal norm does not have legal binding force in the domestic courts of Indonesia without an implementing legislation. Indonesia is a dualist country vis-à-vis the relation of international law and national law. In regard with the implementation of rules of international law into the Indonesian courts, Indonesia follows the transformation theory where the rules of international law must be transposed into national laws to have them enforced. Therefore, it is the supremacy of national law over international law before the domestic courts.